2021
DOI: 10.3390/ph14060572
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of a Library of Thioxanthones and Their Potential as Efflux Pump Inhibitors

Abstract: The overexpression of efflux pumps is one of the causes of multidrug resistance, which leads to the inefficacy of drugs. This plays a pivotal role in antimicrobial resistance, and the most notable pumps are the AcrAB-TolC system (AcrB belongs to the resistance-nodulation-division family) and the NorA, from the major facilitator superfamily. In bacteria, these structures can also favor virulence and adaptation mechanisms, such as quorum-sensing and the formation of biofilm. In this study, the design and synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In the interactions of (R,R)-8 in NorA, it can be seen that the substituent in the C3 position was predicted to play an important role in binding to this portion of the efflux system. The amide establishes a hydrogen bond with Glu-222, as did structurally-related thioxanthones previously tested [53], and the hydroxyl moiety can do the same with Phe-288, as can be seen in Figure 3A. Besides, this compound seems to fit perfectly in a pocket present in this site (Figure 3B).…”
Section: Efflux Pump Inhibitionmentioning
confidence: 61%
See 3 more Smart Citations
“…In the interactions of (R,R)-8 in NorA, it can be seen that the substituent in the C3 position was predicted to play an important role in binding to this portion of the efflux system. The amide establishes a hydrogen bond with Glu-222, as did structurally-related thioxanthones previously tested [53], and the hydroxyl moiety can do the same with Phe-288, as can be seen in Figure 3A. Besides, this compound seems to fit perfectly in a pocket present in this site (Figure 3B).…”
Section: Efflux Pump Inhibitionmentioning
confidence: 61%
“…Compound (R)-17 was predicted to interact with several residues previously described for xanthones and thioxanthones, such as Gln-89, Gln-176, and Gly-619 [32,53]. Additionally, this compound also interacts with Ser-180, Gln-181, and Gln-273 (Figure 4C).…”
Section: Efflux Pump Inhibitionmentioning
confidence: 67%
See 2 more Smart Citations
“…For the Gram-positive, S. aureus 272123, a clinical oxacillin- and methicillin-resistant strain, was used. This strain was used to compare the activity of the isolated compounds with that of derivatives previously tested in the same system [ 35 , 36 ]. However, previous studies with this strain suggested that the expression of the norA gene, a core gene of S. aureus , remained unchanged [ 37 ].…”
Section: Resultsmentioning
confidence: 99%